Identification of O-Glcnacylated Proteins in Trypanosoma cruzi - Torres-Gutiérrez, Elia; Pérez-Cervera, Yobana; Camoin, Luc; Zenteno, Edgar; Aquino-Gil, Moyira Osny; Lefebvre, Tony; Cabrera-Bravo, Margarita; Reynoso-Ducoing, Olivia; Bucio-Torres, Martha Irene; Salazar-Schettino, Paz María (Frontiers in Endocrinology, 2019)
Originally an anthropozoonosis in the Americas, Chagas disease has spread from its previous borders through migration. It is caused by the protozoan Trypanosoma cruzi. Differences in disease severity have been attributed to a natural pleomorphism in T. cruzi. Several post-translational modifications (PTMs) have been studied in T. cruzi, but to date no work has focused on O-GlcNAcylation, a highly conserved monosaccharide-PTM of serine and threonine residues mainly found in nucleus, cytoplasm, and mitochondrion proteins. O-GlcNAcylation is thought to regulate protein function analogously to protein phosphorylation; indeed, crosstalk between both PTMs allows the cell to regulate its functions in response to nutrient levels and stress. Herein, we demonstrate O-GlcNAcylation in T. cruzi epimastigotes by three methods: by using specific antibodies against the modification in lysates and whole parasites, by click chemistry labeling, and by proteomics. In total, 1,271 putative O-GlcNAcylated proteins and six modification sequences were identified by mass spectrometry (data available via ProteomeXchange, ID PXD010285). Most of these proteins have structural and metabolic functions that are essential for parasite survival and evolution. Furthermore, O-GlcNAcylation pattern variations were observed by antibody detection under glucose deprivation and heat stress conditions, supporting their possible role in the adaptive response. Given the numerous biological processes in which O-GlcNAcylated proteins participate, its identification in T. cruzi proteins opens a new research field in the biology of Trypanosomatids, improve our understanding of infection processes and may allow us to identify new therapeutic targets.